Encyclopedia of human nutrition - Caballero, Benjamin; Allen, Lindsay; Prentice, Andrew
"This encyclopedia contains signed articles with bibliographies written by an international group of distinguished academics, research scientists, and food-industry professionals. The alphabetical entries cover the scientific, political, and social aspects of nutrition. Among the subjects included are individual nutrients and foods, anatomy and physiology, nutritional therapy for diseases and conditions, and subjects such as nutritional management of refugees, nutrition education, religious customs, and folklore. Appendixes with charts of weights and measures, nutritional allowances, and nutritional content of foods appear in each volume. In-depth coverage of the scientific, political, and social aspects of nutrition set this work apart from other reference sources in the field."--"Outstanding reference sources 2000", American Libraries, May 2000. Comp. by the Reference Sources Committee, RUSA, ALA.
Includes bibliographical references and index.
Keywords: Nutrition -- Encyclopedias; Dietetics -- Encyclopedias